Post‐dialysis fatigue: Comparison of bicarbonate hemodialysis and online hemodiafiltration. Issue 1 (20th November 2022) - Bossola, Maurizio; Monteburini, Tania; Parodi, Emanuele; Santarelli, Stefano; Sirolli, Vittorio; Cenerelli, Stefano; Bonomini, Mario; de Ninno, Grazia; di Stasio, Enrico
Abstract: Introduction: The present cross‐sectional study aimed to compare the prevalence, the characteristics of post‐dialysis fatigue and the length of recovery time after hemodialysis in prevalent end‐stage renal disease patients (ESRD) receiving bicarbonate hemodialysis (HD) or hemodiafiltration (HDF). Methods: Patients were suffering from post‐dialysis fatigue if they spontaneously offered this complaint when asked the open‐ended question: "Do you feel fatigued after dialysis?". Moreover, each patient was invited to rate the intensity, duration, and frequency of post‐dialysis fatigue from 1 to 5. In order to assess RECOVERY TIME AFTER DIALYSIS, patients were invited to answer to the following single open‐ended question: "How long does it take you to recover from a dialysis session?" Findings: We included 335 patients: 252 received HD and 83 received HDF. Post‐dialysis fatigue was present in 204 patients (60.9%). Prevalence of post‐dialysis fatigue did not differ significantly between patients on HD (62.3%) and on HDF (56.6%; p  = 0.430). Median recovery time after dialysis was 180 min [180–240] and did not differ significantly between the two subgroups (180 min [130–240] and 240 min [120–332] p  = 0.671, respectively). Median post‐dialysis fatigue intensity, duration, and frequency were 3 [1–5], 3 [1–5], and 4 [1–5] and did not differ significantly between patients on HD and on HDF. At the multivariate analysis, age, ADL and hemoglobin levels were the independent predictors of the HDF treatment. Discussion: Prevalence and characteristics of post‐dialysis fatigue do not differ significantly between patients receiving bicarbonate HD or HDF.